2006
DOI: 10.1097/01.ta.0000239500.71419.58
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Muscle Tissue Oxygenation in Critically Injured Patients: A Prospective Observational Study

Abstract: PmO2 is a responsive, reliable and continuous monitor of changes in base deficit. Initial low values for either PmO2 or StO2 were associated with post-injury complications. PmO2 monitoring may be useful in identifying patients in the state of occult underresuscitation who remain at risk for developing infection and MOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 36 publications
3
56
0
1
Order By: Relevance
“…Because of better survival in patients with lactate[5 mmol/L, the authors even suggested a protective effect following brain injury. We did not observe such an effect, which may be either be due to more severe head injuries in our patients or as a result of occult hypoperfusion, a known risk factor for subsequent infectious complications [21,22].…”
Section: Discussionmentioning
confidence: 60%
“…Because of better survival in patients with lactate[5 mmol/L, the authors even suggested a protective effect following brain injury. We did not observe such an effect, which may be either be due to more severe head injuries in our patients or as a result of occult hypoperfusion, a known risk factor for subsequent infectious complications [21,22].…”
Section: Discussionmentioning
confidence: 60%
“…The current end points used to guide resuscitation, such as blood pressure, urine output, heart rate, base deficit, and serum lactate levels, are global markers that may underestimate occult tissue hypoperfusion. In the future, more sensitive measures of tissue oxygenation involving polarographic or near-infrared technologies 65 and markers of inflammation and coagulation 66,67 that better reveal the physiologic condition of a patient are likely to replace simple temporal distinctions. They will provide more accurate criteria with which to determine when a patient is ''ready'' for definitive internal fixation of a femoral shaft fracture or other major orthopaedic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…3 Hypoperfusion is the most common event preceding the onset of multiple organ dysfunction syndrome (MODS) during shock resuscitation. 4 Detecting subtle changes in perfusion is crucial to ensure adequate tissue oxygenation and perfusion. Assessments of blood pressure, heart rate, arterial oxygen saturation, central venous pressure, blood gases, urine output, and hemoglobin concentration are used by the trauma team during resuscitation.…”
Section: Authormentioning
confidence: 99%